The Impact of Leadership Styles, Work Discipline, and Work Environment on Employee Performance - Adly; Handoko, Yunus; Kudyah R, Ike (Al-Qalam Institue, 2025)
This study aims to examine the impact of leadership style, work discipline, and work environment on employee performance in Lontong Pancur Village, Pangkalpinang City, Bangka Belitung Islands Province. The government’s role in providing effective leadership and creating a conducive work environment is crucial for achieving organizational goals, particularly in public service areas such as population administration and welfare. Using a multiple linear regression analysis with SPSS 25, the study surveyed 40 village officials, employing a saturated sampling method. The results indicate that leadership style, work discipline, and work environment all have a positive and significant impact on employee performance. Furthermore, when analyzed together, these factors also positively influence employee performance in Lontong Pancur Village. This research contributes to understanding how effective leadership and a supportive work environment can enhance public sector performance, providing valuable insights for improving employee productivity and organizational effectiveness in local government services.